2007
DOI: 10.1002/pola.22421
|View full text |Cite
|
Sign up to set email alerts
|

Cationic ring‐opening copolymerization behavior of trioxane and seven‐membered cyclic carbonate

Abstract: Cationic ring‐opening copolymerization behavior of trioxane (TOX) and a seven‐membered cyclic carbonate, 1,3‐dioxepan‐2‐one (7CC) is described. When TOX and 7CC were cationically copolymerized under various feed ratios using trifluoromethane sulfonic acid (TfOH) as an initiator in nitrobenzene at 30 °C, 7CC was consumed faster than TOX and the decarboxylation was accompanied to afford the corresponding polyacetal–polycarbonate type copolymers containing poly(oxytetramethylene) units. The copolymer composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…But the copolymerization behavior has remained unclear and is highly related to the properties of the cyclic ethers . Besides the cyclic ethers mentioned above, cyclosiloxanes and cyclic carbonate have also been used to copolymerize with TOX. However, although a huge number of papers and patents have been devoted to the copolymerization of various cyclic monomers with TOX, to our surprise, there are only a few patents on the copolymerization of TOX with oxetane derivatives, and no systematic study has been reported on the influence of the incorporate ratio of oxetanes and the length of alkyl side chain on the oxetanes on the thermomechanical properties of the resultant copolymers…”
Section: Introductionmentioning
confidence: 99%
“…But the copolymerization behavior has remained unclear and is highly related to the properties of the cyclic ethers . Besides the cyclic ethers mentioned above, cyclosiloxanes and cyclic carbonate have also been used to copolymerize with TOX. However, although a huge number of papers and patents have been devoted to the copolymerization of various cyclic monomers with TOX, to our surprise, there are only a few patents on the copolymerization of TOX with oxetane derivatives, and no systematic study has been reported on the influence of the incorporate ratio of oxetanes and the length of alkyl side chain on the oxetanes on the thermomechanical properties of the resultant copolymers…”
Section: Introductionmentioning
confidence: 99%
“…This most likely results from their picky synthesis and purification that require a good control of the operating parameters, especially of temperature since these monomers are rather thermally unstable. To date, the only few reported seven-membered ring monomers include the unsubstituted 7CC and the α-methyl, α-phenyl, β-phenyl, β-allyl, dimethyl isopropylidene, tert -butyldiphenylsilyloxy, or bis(naptol) functionalized congeners (Scheme ). These monomers have been polymerized through either cationic or anionic procedures using enzymes, CF 3 COOH, TfOH (Tf = CF 3 SO 2 ), MeOTf, HCl, BCl 3 , BF 3 ·OEt 2 , [Ph 3 C] + [BF 4 ] − , HSbF 6 , or metallic initiators/catalysts such as alkyl alkaline metals, tin derivatives (SnCl 4 , Sn(2-ethylhexanoate) 2 ), Al(O i Pr) 3 , ZnEt 2 -H 2 O, {bis(phenolate)}TiX 2 (X = Cl, O i Pr), or [Cp 2 ZrMe] + [B(C 6 F 5 ) 4 ] − . However, most of the investigations on the ROP of these 7CCs revolved around the unsubstituted monomer.…”
Section: Introductionmentioning
confidence: 99%
“…However, ROP of LA by PEG in the presence of monomer activators has been much less explored. To date, activated monomer ROP of cyclic ester monomers by PEG in the presence of monomer activators has been achieved only for valerolactone, ε‐caprolactones, and cyclic carbonates, using HCl or an organic acid 16–21. Comparatively, ROP of LA by PEG in the presence of monomer activators was not extensive, even under optimal conditions.…”
Section: Introductionmentioning
confidence: 99%